Assessment of Wound-Healing Properties of Medicinal Plants: The Case of Phyllanthus muellerianus - Boakye, Yaw D.; Agyare, Christian; Ayande, George P.; Titiloye, Nicholas; Asiamah, Emmanuel A.; Danquah, Kwabena O. (Frontiers in Pharmacology, 2018)
Phyllanthus muellerianus (Family Euphorbiaceae) is a shrub, which is widely distributed in West Africa and employed traditionally as a wound-healing agent especially in Ghana. The aim of the study was to determine the in vivo wound-healing activity of aqueous aerial part extract of P. muellerianus (PLE) and its major isolate, geraniin. Excision and incision wound models were used to determine the wound-healing activity. Wounds were treated with PLE (0.25, 0.5, and 1% w/w) and geraniin (0.1, 0.2, and 0.4% w/w) aqueous creams. PLE and geraniin significantly (p < 0.001) increased wound contraction rate and hydroxyproline production compared to untreated wounds. Histological studies of wound tissues showed high levels of fibroblasts and increased collagen content and cross-linking in PLE and geraniin-treated wound tissues. Immuno-histochemical investigations revealed high levels of TGF-β1 in PLE and geraniin-treated wound tissues compared to the untreated wound tissues. Tensile strength of incised wounds was significantly (p < 0.05) high in PLE and geraniin-treated wounds. PLE (0.1–100 μg/mL) significantly (p < 0.001) reduce LDH release from HaCaT-keratinocytes compared to the untreated cells. PLE and geraniin possess wound healing and cytoprotective effect.